Design and performance analysis of link-by-link congestion avoidance algorithm. (24th April 2020) - Thombre, Sneha; Patnaik, Lalit M.; Tavildar, Anil S.
In this paper, a simple but new approach, namely link-by-link congestion avoidance (LbLCA) algorithm, which works at the network layer, has been proposed. LbLCA is a proactive congestion avoidance algorithm. It uses explicit feedback to prevent congestion to happen in the first place. The novelty of LbLCA is that no per flow information is required, which makes it more scalable. Based on the design philosophy and equations, sizing of various router buffers has been arrived at for different typical network topologies. Buffer sizes depend upon the mean arrival rate at router input and outgoing link capacities and are independent of round trip time (RTT) and the number of flows passing through the router. The buffer sizes determined using LbLCA design are validated using extensive NS2 simulations. The performance evaluation has been done using NS2 simulations on the typical network topologies. The performance comparison between TCP and LbLCA reveals that proposed LbLCA algorithm gives improved performance for the end-to-end delay and packet delivery ratio. LbLCA is impartial to all flows, as LbLCA works at network layer and therefore, cannot differentiate between flows.